The Persian gamble [compact disc, unabridged] - Rosenberg, Joel C., 1967- (Brilliance Audio, 2019)
Former Secret Service agent Marcus Ryker must track down nuclear weapons before they fall into the wrong hands by infiltrating enemy territory and forging an alliance with a Russian double agent.